Safety Assessment Method for Parallel Runway Approach Based on MC-EVT for Quantitative Estimation of Collision Probability - Yike Li; Honghai Zhang; Zongbei Shi; Jinlun Zhou; Wenqing Li (Aerospace)
The construction of parallel runways is an effective solution to address the constraints of urban land resources and mitigate flight delays caused by the increasing volume of air traffic. To ensure the safety of parallel approach operations and further enhance operational efficiency, this study proposes a quantitative safety risk assessment method for parallel approaches based on Monte Carlo simulation (MCS) and extreme value theory (EVT). Taking a parallel runway at a major airport in Southwest China as a case study, historical Automatic Dependent Surveillance-Broadcast (ADS-B) trajectory data were processed and analyzed to derive traffic flow characteristics and the actual distribution of approach performance. Subsequently, we developed a collision probability estimation model for parallel approaches based on Monte Carlo–extreme value theory (MC-EVT). Monte Carlo simulation was employed to conduct simulation experiments on the parallel approach process, and the collision risk was quantitatively assessed by integrating experimental data with an analysis based on extreme value theory. Finally, taking the parallel runways of a major airport in southwest China as a case study, experiments were conducted under various parallel approach scenarios to quantitatively assess the collision risk between aircraft. The experimental results indicate that the MC-EVT-based safety risk assessment method for parallel approaches reduces the reliance on traffic flow assumptions. Compared to the conventional Monte Carlo method, it achieves a faster convergence rate, significantly reduces computational workload, and improves computational efficiency by a factor of ten, thus demonstrating that the proposed method is capable of accurately and effectively quantifying low-probability collision risks. Furthermore, the findings reveal a strong correlation between parallel runway width and collision risk. The approach risk under a mixed-aircraft-type configuration is higher than that of a single-aircraft-type configuration, while offset approaches can enhance approach safety. This study can provide valuable references for the construction of parallel runways and the development of regulatory frameworks for parallel approach operations in China.